1970
DOI: 10.3126/kumj.v7i3.2724
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive open lumbar discectomy: An alternative to microlumbar discectomy

Abstract: Background: Lumbar disc surgery has come a long way since its fi rst description by Dandy in 1929 1 . Evolving through the transdural approach and a laminectomy for the removal of a disc, it now surpasses the primal technique with essentially a minimally invasive procedure, an extradural approach without laminectomy 2 . Objective: The objective of this study is to ascertain the effectiveness of Minimally Invasive Open Lumbar Discectomy in the treatment of lumbar disc prolapse. Materials and methods:It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Immediate pain relief was seen in 98.33% in Devkota et al series, 97.5% in PS Ramani series, 96% in Yash Gulati series and 90% in CJ Koebbe et al series. 55,56,57,58 In this study immediate radicular pain relief was seen in 96% of cases comparable to other studies.…”
Section: Bhattarai Et Alsupporting
confidence: 88%
“…Immediate pain relief was seen in 98.33% in Devkota et al series, 97.5% in PS Ramani series, 96% in Yash Gulati series and 90% in CJ Koebbe et al series. 55,56,57,58 In this study immediate radicular pain relief was seen in 96% of cases comparable to other studies.…”
Section: Bhattarai Et Alsupporting
confidence: 88%
“…Among three published Nepalese articles on LDH surgery, only two have mentioned outcome after surgery after follow up period of 6-24 months, but have not analyzed variables that influence outcome. [9][10][11] The objective of the current retrospective study is to evaluate different clinical variables related to LDH which can affect outcome after LDH surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In 1929, Dandy et al described two patients with severe CESR, and the dura mater of both patients had been opened and the herniated intervertebral disc was removed through the dural sac [27]. Similarly, Schneider et al reported 2 cases of CESR with lumbar disc herniation into dural sac [28].…”
Section: Discussionmentioning
confidence: 99%